2013
DOI: 10.1039/c2dt32605a
|View full text |Cite
|
Sign up to set email alerts
|

Dual sensing of fluoride ions by the o-carborane–triarylborane dyad

Abstract: The o-carborane-triarylborane dyad shows high fluoride ion affinity through the trigonal-planar boron center while degradation to nido-carborane leads to a turn-on fluorescence response toward fluoride.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 29 publications
0
33
1
Order By: Relevance
“…In contrast to the nonemissive nature of 1 in the solution state, the emission spectra of 2 and 3 in THF at 298 K exhibited weak‐to‐moderate emission bands ( λ em = 352 nm for 2 and 363 nm for 3 ). This feature is different from that found for the para ‐substituted di‐ o ‐carborane compounds, as well as other o ‐carborane derivatives,, [29a], which are almost nonemissive in solution. For the para ‐substituted di‐ o ‐carboranes, it was suggested that the substantial conjugation between two carborane cages and a central phenylene ring, which is coupled with the C–C bond variation of o ‐carborane, was responsible for the emission quenching in solution .…”
Section: Resultscontrasting
confidence: 77%
“…In contrast to the nonemissive nature of 1 in the solution state, the emission spectra of 2 and 3 in THF at 298 K exhibited weak‐to‐moderate emission bands ( λ em = 352 nm for 2 and 363 nm for 3 ). This feature is different from that found for the para ‐substituted di‐ o ‐carborane compounds, as well as other o ‐carborane derivatives,, [29a], which are almost nonemissive in solution. For the para ‐substituted di‐ o ‐carboranes, it was suggested that the substantial conjugation between two carborane cages and a central phenylene ring, which is coupled with the C–C bond variation of o ‐carborane, was responsible for the emission quenching in solution .…”
Section: Resultscontrasting
confidence: 77%
“…Within each series, the 8‐R group on the nido ‐carborane was varied among H, Me, i ‐Pr, and Ph groups to exert different steric and electronic effects (Scheme ). All nido compounds were readily obtained from deboronation of the carborane cage of the corresponding closo ‐carborane substituted triarylboranes with tetrabutylammonium fluoride (TBAF) in refluxing THF (see the Supporting Information). Broad 1 H NMR resonances centered at δ −2.2 to −2.4 ppm indicate the B‐H‐B bridging hydrogen of the nido ‐carborane moiety, while 11 B NMR signals at δ ca.…”
Section: Methodsmentioning
confidence: 98%
“…Along with the strong emission, weak high‐energy bands are concomitantly observed for nido ‐ m2 – m4 and nido ‐ p3 in the region of 360–440 nm. The absence of the high‐energy band in the rigid state, such as a PMMA film (Supporting Information, Figure S12), indicates that the bands can be ascribed to local emission from the PhBMes 2 moiety . PL quantum yields (PLQY, Φ PL ) of nido ‐ m1 – m4 measured in oxygen‐free THF solutions show that nido ‐ m1 and ‐ m4 are moderately emissive whereas nido ‐ m2 and ‐ m3 are poorly emissive ( Φ PL =3–4 % in THF).…”
Section: Methodsmentioning
confidence: 99%
“…For instance, based on the high affinity between boron and fluoride, boron‐containing conjugated materials are often applicable for luminescent fluoride sensors . As another example regarding carborane, the compound at the focus of this Minireview, a ratiometric probe was accomplished with a nido ‐carborane—triphenylborane dyad . From the standpoint of the effective usage of heteroatoms, we recently proposed a new concept for material design based on an “element‐block”, which is the minimum functional unit containing heteroatoms .…”
Section: Introductionmentioning
confidence: 99%